2022
DOI: 10.1038/s41598-022-05099-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased physical activity improves gut microbiota composition and reduces short-chain fatty acid concentrations in older adults with insomnia

Abstract: Physical activity (PA) can improve functional abilities, well-being, and independence in older adults with insomnia. Studies have shown that PA may be linked to changes in the gut microbiota composition and its metabolites’ concentrations. This association among older adults with insomnia, however, is yet to be determined. We explored the relationships between physical activity (PA) levels, gut microbiota composition, and short-chain fatty acid (SCFA) levels in this population. Forty-nine community-dwelling ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 56 publications
(52 reference statements)
4
24
1
Order By: Relevance
“…Pentanoic acid reduces synaptic dysfunction and behavioral deficits due to MA-induced neuroinflammation by inducing IL-10 production [ 75 , 76 ]. Studies have shown that increased physical activity leads to lower SCFA concentrations in older patients with insomnia [ 77 ], and this paper found that hexanoic acid, isovaleric acid, and pentanoic acid all began to decline as well after 2 weeks of moderate-intensity aerobic exercise, which is consistent with the results of the previous study. However, more studies have shown that higher aerobic capacity corresponds to a higher SFCA production rate [ 78 ].…”
Section: Discussionsupporting
confidence: 91%
“…Pentanoic acid reduces synaptic dysfunction and behavioral deficits due to MA-induced neuroinflammation by inducing IL-10 production [ 75 , 76 ]. Studies have shown that increased physical activity leads to lower SCFA concentrations in older patients with insomnia [ 77 ], and this paper found that hexanoic acid, isovaleric acid, and pentanoic acid all began to decline as well after 2 weeks of moderate-intensity aerobic exercise, which is consistent with the results of the previous study. However, more studies have shown that higher aerobic capacity corresponds to a higher SFCA production rate [ 78 ].…”
Section: Discussionsupporting
confidence: 91%
“…Barton et al reported that the gut microbiota diversity, levels of SCFAs, and TMAO of athletes are richer and higher than that of ordinary people with different gut microbiota composition [136], consistent with other studies [137,138]. But Magzal et al indicated that SCFAs level is higher in people with less exercise [139]. Exercise may attenuate LPS-induced memory impairment [140].…”
Section: The Role Of Physical Activitymentioning
confidence: 53%
“…Ruminococcus gnavus is connected to Crohn's disease through its pro-inflammatory product, glucorhamnan polysaccharide ( 61 ), and is associated with metabolic syndrome ( 62 ). By contrast, the microbiome of esports players and students was enriched in beneficial Bacteroides species: B. thetaiotaomicron contributes to an increase in mucus production and strengthening of the epithelial barrier ( 63 ), and has anti-inflammatory properties that inhibit the development of Crohn's disease ( 64 ), while B. uniformis is negatively correlated with physical activity in older adults ( 65 ), alleviates obesity in conjunction with an appropriate diet ( 66 ) and enhances endurance exercise performance ( 67 ). To summarize, our findings confirm changes in the relative abundance of different taxa reported in professional rugby players ( 44 ), marathon runners ( 58 ), professional cyclists ( 68 ), and other sports persons ( 69 ), as well as in elderly healthy individuals with a lifelong history of endurance training ( 46 ) and premenopausal women after continuous physical activity ( 12 ).…”
Section: Discussionmentioning
confidence: 99%